Influence of natural organic matter on chemical composition of broiler chicken carcass - Galimzhan K. Duskaev; Olga V. Kvan; Yaroslav A. Sizentsov; Marina Y. Kurilkina; Bayer S. Nurzhanov (RUDN Journal of Agronomy and Animal Industries)
Intensively developing poultry industry requires a constant search for new methodological approaches to increase not only quantity, but also quality of finished products. Due to the ban on the use of feed antibiotics, more and more research has been carried out aimed at the use of various growth stimulants of plant origin. In our research, a systematic analysis of the effect of vanillin at concentrations of 0.25 mg/kg of the main diet (group 1), 0.50 mg/kg (group 2) and 0.75 mg/kg (group 3) was carried out. The degree of influence was assessed by means of weekly weighing (live weight), determination of chemical composition, macro- and essential elements. The experimental data obtained showed that of all the concentrations of vanillin used, the most pronounced positive dynamics was observed after the use of 0.25 mg/kg of feed, since at the final stage average indicators of the final body weight in this group exceeded the control values by 22.16% ( p 0.05). Indicators of chemical composition indicated the maximum level of protein and ash residue against the background of the minimum values of water and fat in the studied biological samples. The studied indicators of the elemental status also indicated a positive effect of this concentration on percentage of accumulation with the maximum values of calcium, sodium and zinc. Therefore, vanillin at a dose of 0.25 mg/kg of the main diet can be recommended as an effective feed additive.